Affective Empathy, Theory of Mind and Social Functioning in Patients With Focal Epilepsy - Metternich, Birgitta; Wagner, Kathrin; Geiger, Maximilian J.; Schulze-Bonhage, Andreas; Hirsch, Martin; Schönenberg, Michael (Frontiers in Psychiatry, 2022)
Objective: Social cognition comprises basic and more complex functions, such as theory of mind (ToM) and affective empathy. Although everyday social interactions may be impaired if such higher-order social cognitive functions are compromised, associations between social functioning and social cognition in people with focal epilepsy (PWFE) are still poorly understood. We used a novel, naturalistic approach to investigate ToM in PWFE by applying the Movie for the Assessment of Social Cognition (MASC). Furthermore, we studied affective empathy, the relationship between social cognitive parameters and measures of social functioning, as well as between epilepsy focus and ToM. Methods: 30 patients with either temporal (TLE) or frontal lobe epilepsy (FLE) were compared to 29 healthy control subjects (HC). In addition to the MASC, we applied questionnaire measures assessing empathy and everyday social functioning. Results: PWFE, especially with FLE, performed significantly worse than HC on the MASC. Perceived social integration and social activities, but not affective empathy, were reduced in PWFE. Regression analyses revealed associations between perceived social integration, clinical group status, affective empathy and ToM. Conclusion: PWFE displayed ToM deficits during a naturalistic task, whereas affective empathy was unimpaired. FLE may be associated with especially compromised ToM performance. Social cognition and social functioning appear to be interrelated in PWFE, whose self-perceived levels of social integration and social activities are lower than those of HC. More research into the association between social cognition and social functioning in PWFE is needed, in order to develop tailored intervention programs for these patients.